2009
DOI: 10.2106/jbjs.h.01121
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Postoperative Passive Motion on Rotator Cuff Healing in a Rat Model

Abstract: In this model, immediate postoperative passive motion was found to be detrimental to passive shoulder mechanics. We speculate that passive motion results in increased scar formation in the subacromial space, thereby resulting in decreased range of motion and increased joint stiffness. Passive motion had no effect on collagen organization or tendon mechanical properties measured six weeks after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 33 publications
0
83
0
3
Order By: Relevance
“…The humeral diaphysis was potted in polymethylmethacrylate and placed in a base fixture. Specimens were submerged in a 37°C phosphatebuffered saline bath and tensile tested using an Instron 5543 mechanical test frame (Instron Corp, Norwood MA, USA) using a protocol described previously [3,21]. Briefly, tendons were subjected to 10 cycles of preconditioning between 0.1 and 0.5 N to provide consistent strain history between specimens and then allowed to return to equilibrium over 300 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…The humeral diaphysis was potted in polymethylmethacrylate and placed in a base fixture. Specimens were submerged in a 37°C phosphatebuffered saline bath and tensile tested using an Instron 5543 mechanical test frame (Instron Corp, Norwood MA, USA) using a protocol described previously [3,21]. Briefly, tendons were subjected to 10 cycles of preconditioning between 0.1 and 0.5 N to provide consistent strain history between specimens and then allowed to return to equilibrium over 300 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have therefore turned to animal models to study rotator cuff pathology. When making decisions about repair options, clinicians often refer to animal studies of rotator cuff injury that include mice (Thomopoulos et al, 2007), rats (Soslowsky et al, 1996), sheep (Gerber et al, 1999), rabbits (Björkenheim, 1989), dogs (Kujat, 1990), goats and others (Adams et al, 2006;Das et al, 2011;Grumet et al, 2009;MacGillivray et al, 2006;Peltz et al, 2009;Uggen et al, 2010). Although a variety of animal models have been used to study rotator cuff disease, questions remain about their relevance to humans, because of differences in their basic muscle architecture, bony anatomy and healing capacity (Brand, 2008;Dourte et al, 2010;Soslowsky et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Another animal model has shown that immediate early passive motion should be avoided and that delayed passive motion had no negative effect on the strength and maturity of the remodeled tendon [16]. Early passive motion may stimulate excessive matrix formation and increased scar formation in the subacromial space which leads to worsening passive shoulder mechanics, increased stiffness, and loss of motion [17]. A 2-week period of immobilization helps extracellular matrix represent similar characteristics of uninjured tissue.…”
Section: Range Of Motionmentioning
confidence: 99%